Preparation method and application of a bifunctional ion salt passivated tin-based perovskite film and its perovskite solar cell
By introducing bifunctional ionic salt ethylenediamine formate at the interface of the tin-based perovskite film and depositing the film by the antisolvent method, the problems of divalent tin instability and surface defects in tin-based perovskite solar cells are solved, and its photoelectric conversion efficiency and stability are significantly improved.
Patent Information
- Application Number
- CN202110959642.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-08-20
AI Technical Summary
Tin-based perovskite solar cells have insufficient photoelectric conversion efficiency and stability due to the instability and many surface defects of divalent tin.
The bifunctional ionic salt ethylenediamine formate was introduced at the interface of the tin-based perovskite film to reduce surface defects through strong interactions and improve the thermodynamic stability of divalent tin. The film was deposited by the anti-solvent method and annealed to obtain a flat and dense film.
The photoelectric conversion efficiency and long-term stability of tin-based perovskite solar cells are significantly improved, the surface defects are reduced, the crystal orientation is perpendicular to the substrate, and the device can maintain an initial efficiency of 95% under an unencapsulated nitrogen atmosphere.
Smart Images

Figure CN114284440B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for surface passivation and anti-oxidation dual-functional interface treatment of tin-based perovskite solar cells, belonging to the field of optoelectronic materials and devices. The invention uses a special dual-functional ion salt ethylenediamine formate to treat the upper interface of tin-based perovskite and uses an anti-solvent method to prepare a tin-based perovskite film on an ITO transparent conductive glass deposited with a hole transport material. After the upper interface is treated and annealed, the film surface is flat and dense, the defect state density is low, and the crystal orientation is perpendicular to the substrate. The prepared tin-based perovskite solar cell has excellent photoelectric conversion efficiency and outstanding device stability. Background Art
[0002] As human beings' demand for energy continues to expand, traditional fossil energy can no longer meet human beings' current needs. Solar energy, as an inexhaustible clean energy, is considered to be one of the clean energy sources that can gradually replace traditional fossil energy. As the main carrier for converting solar energy into electrical energy, solar cells have received extensive attention from industry personnel. At present, the solar cells that have been widely commercialized are mainly concentrated in monocrystalline silicon and polycrystalline silicon cells. However, the production and processing of crystalline silicon solar cells involve a series of problems. For example, energy consumption is high and environmental pollution is serious. Therefore, under the current requirements of sustainable development and green development, it is difficult to have further development space.
[0003] Since the advent of organic-inorganic hybrid perovskite solar cells in 2009, their photoelectric conversion efficiency has increased from 3.8% to 25.5% in just a few decades. Although the photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has developed rapidly, they also face many problems in the process of commercial application. First of all, lead-based perovskite solar cells contain highly toxic lead elements, so it is urgent to find a low-toxic element that can replace lead.
[0004] At present, tin-based perovskite materials are considered to be one of the most promising alternatives to lead-based perovskites because of their low environmental and biological toxicity, low exciton binding energy and narrow optical band gap. However, since the divalent tin in the tin-based perovskite system is in a thermodynamically unstable state, it is very easy to be oxidized to tetravalent tin. In addition, due to the fast crystallization rate during its preparation process, it has more surface defects. The above two major problems are not conducive to the preparation of high-efficiency temperature tin-based perovskite solar cells. For this reason, by introducing a passivation molecular layer with double high energy on the interface of tin-based perovskite, its final energy conversion efficiency and long-term working stability can be effectively improved. After the surface of the tin-based perovskite film is treated by the special bifunctional ion salt ethylenediamine formate, the surface defects of the tin-based perovskite can be effectively reduced through the strong interaction between molecules, thereby obtaining a tin-based perovskite film with low defect state density, smooth and dense surface, and highly vertical orientation of the crystal. In addition, the bifunctional ion salt ethylenediamine formate can also improve the thermodynamically unstable characteristics of divalent tin, thereby improving its long-term stability. Ultimately, the performance and stability of tin-based perovskite solar cells prepared by the antisolvent method were significantly improved. Summary of the invention
[0005] The present invention proposes a method for preparing a dual-functional ion salt passivated tin-based perovskite film and a perovskite solar cell, which is a method for surface passivation and anti-oxidation dual-functional interface treatment of tin-based perovskite solar cells, and solves the technical problem of many defects on the interface of tin-based perovskites and the instability of divalent tin itself. A dual high-energy passivation molecular layer is introduced on the interface of tin-based perovskites to effectively passivate the defects on the interface, and the stability of divalent tin is improved by changing the chemical environment around divalent tin, thereby preparing a tin-based perovskite film with a smooth and dense surface, low defect state density, and a crystal orientation perpendicular to the substrate and a method for preparing a highly efficient and stable tin-based perovskite solar cell, comprising the following steps:
[0006] The divalent tin in the tin-based perovskite system is in a thermodynamically unstable state and is easily oxidized to tetravalent tin. In addition, due to the fast crystallization rate during its preparation process, it has many surface defects. In view of the above problems, it is proposed to introduce a bifunctional ion salt ethylenediamine formate on the interface of tin-based perovskite, thereby greatly improving the thermodynamic instability of divalent tin, thereby improving its long-term stability, thereby effectively passivating the defects on its interface, and improving the stability of divalent tin by changing the chemical environment around divalent tin, and preparing a tin-based perovskite film with a smooth and dense surface, low defect state density, and a crystal orientation perpendicular to the substrate, and a method for preparing a highly efficient and stable tin-based perovskite solar cell.
[0007] In order to solve the technical problem of the present invention, a technical solution is proposed: a method for preparing a bifunctional ion salt passivated tin-based perovskite film and a perovskite solar cell thereof, comprising the following steps:
[0008] (1) Butylamine acetate, formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a molar ratio of 2:3:4:0.6 (volume ratio of 4:1), and guanidine iodide is added as an additive to prepare a low-dimensional tin-based perovskite precursor solution, and stirred at 30-120° C. for 1-4 hours; phenylethylamine hydrochloride, formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a molar ratio of 2:3:4:0.6 (volume ratio of 4:1), and guanidine iodide is added as an additive to prepare a low-dimensional tin-based perovskite precursor solution. Tin-based perovskite precursor solution 2 is stirred at 30-120°C for 1-4 hours; formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide at a molar ratio of 1:1:0.1 (volume ratio of 4:1), and guanidine iodide and ammonium thiocyanate are added as additives to prepare tin-based perovskite precursor solution 3, which is stirred at 30-120°C for 1-4 hours; low-dimensional tin-based perovskite precursor solution 1, low-dimensional tin-based perovskite precursor solution 2 and tin-based perovskite precursor solution 3 are mixed at a molar ratio of 1-10:1-10:1-10, and stirred at 30-120°C for 1-4 hours;
[0009] (2) spin coating and depositing hole transport material on the cleaned and treated ITO transparent conductive glass;
[0010] (3) preheating the ITO transparent conductive glass deposited with the hole transport material and the prepared tin-based perovskite precursor solution;
[0011] (4) depositing a tin-based perovskite film on a preheated ITO transparent conductive glass deposited with a hole transport material using an anti-solvent method;
[0012] (5) depositing cationic ethylenediamine and anionic formic acid on the deposited tin-based perovskite film, respectively, and after annealing, obtaining a flat and dense tin-based perovskite film with low defect state density and a crystal orientation perpendicular to the substrate;
[0013] (6) vacuum thermally evaporating an electron transport material on the tin-based perovskite film;
[0014] (7) Thermally evaporate the interface modification material and metal electrode onto the electron transport material.
[0015] Preferably, in the step (1), the concentrations of the low-dimensional tin-based perovskite precursor solution 1, the low-dimensional tin-based perovskite precursor solution 2 and the tin-based perovskite precursor solution 3 are all 100-600 mg / mL; the amount of the guanidine iodide additive in the step (1) is 5wt% of the tin-based perovskite precursor solution; the amount of the ammonium thiocyanate additive in the step (1) is 3wt% of the tin-based perovskite precursor solution; in the step (1), the mixing molar ratio of the low-dimensional tin-based perovskite precursor solution 1, the low-dimensional tin-based perovskite precursor solution 2 and the tin-based perovskite precursor solution 3 is 3:7:2.5.
[0016] Preferably, the hole transport material deposited on the transparent ITO conductive glass in step (2) is PEDOT:PSS, and the specific steps are: after spin coating PEDOT:PSS, annealing at 120° C. for 30 minutes.
[0017] Preferably, in the step (3), the transparent ITO conductive glass deposited with the hole transport material and the prepared tin-based perovskite precursor solution are preheated at a temperature of 40-80° C. and a preheating time of 1-5 min.
[0018] Preferably, the anti-solvent used in the anti-solvent method in step (4) is anhydrous chlorobenzene, and the amount used is 0.1-0.8 mL.
[0019] Preferably, the concentration of ethylenediamine used in step (5) is 0.025 mol / L chlorobenzene solution, and the concentration of formic acid used is 0.05 mol / L chlorobenzene solution. The specific steps are: after spin coating, annealing at 80° C. for 5 min.
[0020] Preferably, the electron transport material thermally evaporated in step (6) is C 60 , thickness is 50nm.
[0021] Preferably, in step (7), the interface modification material is LiF, the metal electrode is Al, and the specific steps are:
[0022] (1) LiF is thermally evaporated on the electron transport layer with a thickness of 1 nm;
[0023] (2) The thickness of the metal Al electrode is 100 nm.
[0024] In order to solve the technical problem of the present invention, another technical solution is proposed: a perovskite solar cell prepared by a preparation method of a tin-based perovskite film passivated by any bifunctional ion salt and a perovskite solar cell thereof.
[0025] In order to solve the technical problem of the present invention, another technical solution is proposed: application of the bifunctional ion salt passivated tin-based perovskite film and tin-based perovskite solar cell in the optoelectronic field.
[0026] Beneficial effects of the present invention:
[0027] (1) The method of using an appropriate amount of bifunctional ion salt for interface treatment can effectively passivate the defects on the interface and improve the stability of divalent tin by changing the chemical environment around divalent tin, thereby preparing a tin-based perovskite film with a flat and dense surface, a smooth and dense surface, a high degree of vertical orientation, and larger grains;
[0028] (2) After interface treatment, the tin-based perovskite solar cell can still maintain about 95% of the initial efficiency after about 2000 hours in an unpackaged N2 atmosphere. After not undergoing interface treatment, the tin-based perovskite solar cell can only maintain 30% of the initial efficiency after about 2000 hours in an unpackaged N2 atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described below in conjunction with the accompanying drawings.
[0030] Figure 1 The SEM images are of the tin-based perovskite film with low defect state density and smooth and dense surface prepared in a nitrogen atmosphere of the present invention and the tin-based perovskite film prepared by traditional butylamine iodide salt;
[0031] Figure 2 It is a grazing incidence wide-angle X-ray scattering diagram of the tin-based perovskite film prepared in a nitrogen atmosphere of the present invention and the tin-based perovskite film prepared by traditional butylamine iodide salt;
[0032] Figure 3 It is a structural diagram of a tin-based perovskite solar cell device prepared in a nitrogen atmosphere according to the present invention;
[0033] Figure 4 It is a JV curve diagram of the tin-based perovskite solar cell prepared in a nitrogen atmosphere according to the present invention and the tin-based perovskite solar cell prepared by traditional butylamine iodide salt;
[0034] Figure 5 It is a dark current curve diagram of the tin-based perovskite solar cell prepared in a nitrogen atmosphere according to the present invention and the tin-based perovskite solar cell prepared by traditional butylamine iodide salt;
[0035] Figure 6 The graph is a curve showing the change of the photoelectric conversion efficiency of the tin-based perovskite solar cell prepared in a nitrogen atmosphere by the present invention and the tin-based perovskite solar cell prepared by a conventional butylamine iodide salt in nitrogen over time; DETAILED DESCRIPTION
[0036] Example 1
[0037] This embodiment is an inverted planar heterojunction solar cell prepared by a method of passivating a tin-based perovskite film with a low defect state density, a smooth and dense surface, and a high degree of vertical orientation and a tin-based perovskite solar cell thereof by a bifunctional ion salt passivation method of the invention, so as to fully understand the present invention, mainly comprising the following steps:
[0038] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then dried with nitrogen and baked in an oven to obtain a clean ITO substrate.
[0039] Step 2) 60.96 mg of ionic liquid type organic bulk amine molecular salt butylamine acetate, 118.06 mg of formamidine hydroiodide, 340.98 mg of stannous iodide and 86.05 mg of stannous fluoride were dissolved in a mixed solvent of 0.8 mL of N, N-dimethylformamide and 0.2 mL of dimethylformamide, and 26 mg of guanidine iodide was added as an additive to prepare a low-dimensional tin-based perovskite precursor solution 1, which was stirred at 60° C. for 2 hours; 66.55 mg of phenylethylamine hydrochloride, 108.91 mg of formamidine hydroiodide, 314.54 mg of stannous iodide and 79.38 mg of stannous fluoride were dissolved in 0.8 mL of N, N-dimethylformamide and 0.2 mL of dimethylformamide. 164.24 mg of formamidine hydroiodide, 355.76 mg of stannous iodide and 14.1 mg of stannous fluoride were dissolved in 0.8 mL of N,N-dimethylformamide and 0.2 mL of dimethyl sulfoxide mixed solvent, and 15.6 mg of ammonium thiocyanate was added as an additive to prepare tin-based perovskite precursor solution three, which was stirred at 60 ° C for 2 hours; 0.30 mL of low-dimensional tin-based perovskite precursor solution one, 0.70 mL of low-dimensional tin-based perovskite precursor solution two and 0.25 mL of tin-based perovskite precursor solution three were mixed and stirred at 60 ° C for 2 hours;
[0040] Step 3) The ITO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.
[0041] Step 4) Take 50 μL of hole transport material PEDOT:PSS and drop it onto the ITO conductive glass treated in step 3) with a pipette. After spin coating at 5000 rpm for 50 seconds, anneal the ITO coated with PEDOT:PSS at 120°C for 30 minutes.
[0042] Step 5) The ITO conductive substrate coated with the hole transport layer annealed in step 4) and the low-dimensional tin-based perovskite precursor solution prepared in step 1) are placed on a hot plate at 60° C. and preheated for 2 minutes.
[0043] Step 6) Take 75 μL of the preheated perovskite precursor solution in step 5) and drop it onto the preheated ITO substrate in step 5), spin coat it into a film, and then anneal it to obtain a perovskite film. The conditions for spin coating the perovskite precursor solution are 4000 rpm in a nitrogen atmosphere for 60 seconds, annealing at 60° C. for 2 minutes, and annealing at 100° C. for 10 minutes.
[0044] Step 7) Take 75 μL of 0.025 mM ethylenediamine chlorobenzene solution and drop it onto the thin film with tin-based perovskite deposited in step 6) and spin coat it to form a film. The conditions for spin coating the interface layer are 3000 rpm for 30 seconds in a nitrogen atmosphere.
[0045] Step 8) Take 75 μL of 0.050 mM formic acid in chlorobenzene solution and drop it onto the film deposited with ethylenediamine in step 7), spin coat it to form a film, and then anneal it. The conditions for spin coating the interface layer are 3000 rpm for 30 seconds in a nitrogen atmosphere and annealing at 80°C for 2 minutes.
[0046] Step 9) Vacuum thermally evaporate an electron transport material on the tin-based perovskite film. The thermally evaporated electron transport material is C 60 , thickness is 50nm.
[0047] Step 10) Thermally evaporate the interface modification material LiF with a thickness of 1 nm and the metal electrode Al on the electron transport material.
[0048] Step 11) thermally evaporate the metal electrode Al on the interface modification material LiF to a thickness of 100 nm.
[0049] Step 12) Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 9.40%, the open circuit voltage is 0.60V, and the short circuit current is 23.71mA / cm 2 , the filling factor is 66.21%. In addition, the tin-based perovskite solar cells after interface treatment are not encapsulated in N 2 In the atmosphere, the initial efficiency can still be maintained at about 95% after about 2000 hours. The tin-based perovskite solar cells without interface treatment can maintain about 95% of the initial efficiency in the unpackaged N 2 After about 2000 hours in the atmosphere, only 30% of the initial efficiency is retained. 2 The stability data shows that the efficiency can still be maintained at about 90% of the initial efficiency after about 600 hours under the atmosphere, which is also significantly improved.
[0050] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for preparing a bifunctional ion salt passivated tin-based perovskite solar cell, characterized in that: The following steps are involved: (1) Butylamine acetate, formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 2:3:4:0.6, and guanidine iodide is added as an additive to prepare a low-dimensional tin-based perovskite precursor solution 1, and stirred at 30-120°C for 1-4 hours; phenylethylamine hydrochloride, formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 2:3:4:0.6, and guanidine iodide is added as an additive to prepare a low-dimensional tin-based perovskite precursor solution 2, and stirred at 30-120°C for 1-4 hours; formamidine hydroiodide, stannous iodide and stannous fluoride are dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 1:1:0.1 In a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, guanidine iodide and ammonium thiocyanate are added as additives to prepare a tin-based perovskite precursor solution three, and the mixture is stirred at 30-120° C. for 1-4 hours; low-dimensional tin-based perovskite precursor solution one, low-dimensional tin-based perovskite precursor solution two and tin-based perovskite precursor solution three are mixed at a molar ratio of 1-10:1-10:1-10, and the mixture is stirred at 30-120° C. for 1-4 hours; (2) spin coating and depositing hole transport material on the cleaned and treated ITO transparent conductive glass; (3) preheating the ITO transparent conductive glass deposited with the hole transport material and the prepared tin-based perovskite precursor solution; (4) Depositing a tin-based perovskite film on a preheated ITO transparent conductive glass deposited with a hole transport material using an anti-solvent method; (5) depositing cationic ethylenediamine and anionic formic acid on the deposited tin-based perovskite film, respectively, and after annealing, obtaining a flat and dense tin-based perovskite film with low defect state density and a crystal orientation perpendicular to the substrate; (6) Vacuum thermally evaporating an electron transport material onto the tin-based perovskite film; (7) Then thermally evaporate the interface modification material and metal electrode on the electron transport material.
2. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: In the step (1), the concentrations of the low-dimensional tin-based perovskite precursor solution 1, the low-dimensional tin-based perovskite precursor solution 2 and the tin-based perovskite precursor solution 3 are all 100-600 mg / mL; the amount of the guanidine iodide additive in the step (1) is 5 wt% of the tin-based perovskite precursor solution; the amount of the ammonium thiocyanate additive in the step (1) is 3 wt% of the tin-based perovskite precursor solution; and the mixing molar ratio of the low-dimensional tin-based perovskite precursor solution 1, the low-dimensional tin-based perovskite precursor solution 2 and the tin-based perovskite precursor solution 3 in the step (1) is 3:7:2.
5.
3. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: In the step (2), the hole transport material deposited on the transparent ITO conductive glass is PEDOT:PSS, and the specific steps are: after spin coating PEDOT:PSS, annealing at 120°C for 30 min.
4. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: In the step (3), the transparent ITO conductive glass deposited with hole transport material and the prepared tin-based perovskite precursor solution are preheated at a temperature of 40-80° C. for a preheating time of 1-5 min.
5. The method for preparing a bifunctional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: The anti-solvent used in the anti-solvent method in step (4) is anhydrous chlorobenzene, and the amount used is 0.1-0.8 mL.
6. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: The concentration of ethylenediamine used in step (5) is 0.025 mol / L chlorobenzene solution, and the concentration of formic acid used is 0.05 mol / L chlorobenzene solution. The specific steps are: after spin coating, annealing at 80° C. for 5 min.
7. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: The electron transport material thermally evaporated in step (6) is C 60 , with a thickness of 50 nm.
8. The method for preparing a dual-functional ion salt passivated tin-based perovskite solar cell according to claim 1, characterized in that: In the step (7), the interface modification material is LiF, the metal electrode is Al, and the specific steps are: (1) LiF is thermally evaporated on the electron transport layer with a thickness of 1 nm; (2) The thickness of the metal Al electrode is 100 nm.
9. A bifunctional ion salt passivated tin-based perovskite solar cell prepared according to any one of claims 1 to 8.
10. Application of the bifunctional ion salt passivated tin-based perovskite solar cell according to claim 9 in the field of optoelectronics.
Citation Information
Patent Citations
Parallel interdigital full-back contact perovskite solar cell and preparation method thereof
CN111312900A
Low-dimensional tin-based perovskite thin film prepared from ionic liquid type organic large-volume amine molecular salt as well as solar cell and application of low-dimensional tin-based perovskite thin film
CN111952455A